2017
DOI: 10.1371/journal.pone.0173780
|View full text |Cite
|
Sign up to set email alerts
|

IL-22, GM-CSF and IL-17 in peripheral CD4+ T cell subpopulations during multiple sclerosis relapses and remission. Impact of corticosteroid therapy

Abstract: Multiple sclerosis (MS) is thought to be a Th17-mediated dysimmune disease of the central nervous system. However, recent publications have questioned the pathogenicity of IL-17 per se and rather suggest the implication of other Th17-related inflammatory mediators. Therefore, we studied the expression of GM-CSF, IL-22, IL-24, IL-26 and CD39 in peripheral blood mononuclear cells (PBMCs) from MS patients during relapses, remission and following corticosteroid treatment. We performed qPCR to measure mRNA levels f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 51 publications
2
28
1
Order By: Relevance
“…Li et al reported upregulated IL-19 and IL-20 gene expression in PBMC of patients with uveitis [66]. IL-24 was not included in this study, but Muls et al [67] reported that IL-24 (and IL-26) mRNA levels are comparable in relapsing or stable MS, and similar to healthy controls. Since autoreactive T cells are believed to participate in pathogenesis of both these diseases [68, 69], and in view of the reported ability of IL-20R cytokines to regulate T cells responses, further studies exploring the potential roles of IL-20R cytokines in CNS diseases would be of interest.…”
Section: Il-20r Cytokines In Autoimmune Diseasesmentioning
confidence: 89%
See 1 more Smart Citation
“…Li et al reported upregulated IL-19 and IL-20 gene expression in PBMC of patients with uveitis [66]. IL-24 was not included in this study, but Muls et al [67] reported that IL-24 (and IL-26) mRNA levels are comparable in relapsing or stable MS, and similar to healthy controls. Since autoreactive T cells are believed to participate in pathogenesis of both these diseases [68, 69], and in view of the reported ability of IL-20R cytokines to regulate T cells responses, further studies exploring the potential roles of IL-20R cytokines in CNS diseases would be of interest.…”
Section: Il-20r Cytokines In Autoimmune Diseasesmentioning
confidence: 89%
“…Li et al reported up-regulated IL-19 and IL-20 gene expressions in PBMC of patients with uveitis 66. IL-24 was not included in this study, but Muls et al67…”
mentioning
confidence: 80%
“…Of interest, anti-IL-17A humanized neutralizing monoclonal antibody (AIN457 or Secukinumab) injected in patients with MS showed reduction of lesions compared to placebo-treated control subjects [75]. In addition, Th22 cells are highly present in the peripheral blood and cerebral spinal fluid of patients with active RRMS [76], and IL-22 mRNA and Th22 cells are increased in relapsing MS compared to remitting MS patients [77]. Furthermore, Th22 cells specifically recognize MBP and are resistant to IFN-beta therapy [76].…”
Section: T Helper Cellsmentioning
confidence: 99%
“…The results indicate a new diagnosis and treatment target for SLE. There is evidence that IL-22 modulates the inflammatory process and several autoimmune diseases, including SLE, rheumatoid arthritis (RA) and multiple sclerosis (MS) [14][15][16]. In primary Sj€ ogren's syndrome (pSS), both protein and mRNA levels of IL-22 were increased significantly in the inflamed salivary glands.…”
Section: Introductionmentioning
confidence: 99%